ORFeome-based identification of biomarkers for serodiagnosis of Mycobacterium tuberculosis latent infection - Fangbin Zhou; Xindong Xu; Sijia Wu; Xiaobing Cui; Weiqing Pan (BMC Infectious Diseases, 2017)
Abstract Background The challenges posed by Mycobacterium tuberculosis infection require the gradual removal of the pool of latent tuberculosis infection (LTBI). The current cell-immune-based diagnostic tests used to identify LTBI individuals have several irreversible drawbacks. In the present study, we attempted to identify novel diagnostic antigens for LTBI. Methods A high-throughput glutathione S-transferase (GST)-fusion technology was used to express over 409 TB proteins and sera from LTBI and healthy individuals was used to interrogate these GST-TB fusion proteins. Results Of 409 TB proteins, sixty-three reacted seropositive and defined the immuno-ORFeome of latent M. tuberculosis. Within the immuno-ORFeome, the rare targets were predominantly latency-associated proteins and secreted proteins, while the preferentially recognized antigens tended to be transmembrane proteins. Six of novel highly-reactive antigens had the potential to distinguish LTBI from active TB and healthy individuals. A multiple-antigen combination set was selected through analysis of various combinations. A panel of 94 archived serum samples was used to validate the diagnostic performance of the multiple-antigen combination set, which had sensitivity of 66.1% (95% CI 52.9, 77.4) and specificity of 87.5% (95% CI 70.1, 95.1). Conclusion These results provide experimental evidence of the immunogenicity of novel TB proteins that are suitable for the development of serodiagnostic tools for LTBI.